Overview of the Russian Coal Market in the Context of Geopolitical and Economic Turbulence: The European Embargo and New Markets - Panaedova, Galina; Borodin, Alex; Zehir, Cemal; Laptev, Sergey; Kulikov, Andrey (MDPI, 2023)
The energy crisis caused by global structural changes in the political and economic sphere is the reason for the change in Russia's energy strategy based on the concept of sustainable development. The presented study is intended to test the hypothesis about the stimulating effect of economic sanctions on the traditional energy sector and is intended to examine the assumption about the implementation in Russia of the concept of the diversification of energy resources in terms of the use of coal fuel using a systematic approach. The object of empirical research is the Russian Federation in comparison with the leading countries in reserves, exports, and imports of coal raw materials in the period 2010-2021. The tools of scientific research used are based on methods of comparative, economic and statistical analysis, and technologies of consensus expert assessments. The integrated methodological approach applied in the study allows us to present the relationship between energy policy and the government's strategy in achieving the goals of sustainable energy production and the transition to transformational models of using traditional energy sources. This article identifies new opportunities for academic research and discussion of the potential of demand management, the dynamics of consumption and production of traditional energy resources based on the use of avant-garde technologies, and the design of scenarios for the implementation of the energy transition, taking into account various options for economic development and geopolitical changes.
Keywords: engineering; global; Russian coal market; reserves; production; consumption; export of coal raw materials; pricing factors; embargo; new sales markets; transformation of logistics chains; price trends; development prospects; SECTOR; POWER; GAS; OIL; Energy & Fuels